The Role of Notary Honorary Council after Constitutional Court Decision Number: 16/PUU-XVIII/2020 - Nurhadi Nurhadi (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2020)
Public complaints against notaries should be the object of review by the supervisory board based on the code of ethics and applicable laws. When the supervisory panel finds an alleged criminal act in the results of its review, it is important to submit it to the Notary Honorary Council for further action. This study uses a sociological juridical approach (empirical) in a qualitative descriptive manner. This research specification focuses on empirical normative studies, namely legal research equipped with empirical data. The data collection method in this study was carried out by field studies and literature studies. The data obtained were then analyzed qualitatively. The conclusion is that based on the provisions which include Article 66 paragraph (1) UUJN, Constitutional Court Decision Number: 16/PUU-XVIII/2020, Permenkumham No.7/2016, Permenkumham No.15/2020 and MoU No. B/1056/V/2006 Number 01/MOU/PP-INI/V/2006 concerning Development and Enhancement of Professionalism in the Field of Law Enforcement, the role of the Notary Honorary Council must be put forward in connection with the police report No.: LP288/VII/2020 SPKT Polda Sultra after the Constitutional Court decision Number: 16/PUU-XVIII/2020. Whereas the suggestion is that in order to understand the role of the Notary Honorary Council that must be put forward after the Constitutional Court decision Number: 16/PUU-XVIII/2020, socialization is needed in the wider community so that suspected criminal acts by notary persons are not immediately reported to the police but are resolved first through the inspection mechanism in the supervisory board and the honorary council.